2019
DOI: 10.1021/acscatal.9b00151
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Mechanistic Insights of Shaped Catalyst Body Formulations and Their Impact on Catalytic Properties

Abstract: Zeolite-based catalysts are globally employed in many industrial processes, such as in crude-oil refining and in the production of bulk chemicals. However, to be implemented in industrial reactors efficiently, zeolite powders are required to be shaped in catalyst bodies. Scale-up of zeolite catalysts into such forms comes with side effects to its overall physicochemical properties and to those of its constituting components. Although fundamental research into “technical” solid catalysts is scarce, binder effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 59 publications
(100 reference statements)
2
101
0
Order By: Relevance
“…Calculated from the saturation adsorption amounts, the n-hexane to cyclohexane adsorption ratio of HZ-bo increased from 1.8 to 1.9 after regeneration, whereas that of HZ-atp decreased from 1.9 to 1.7 after regeneration. It means that the initial para-selectivity increment for regenerated Z5-bo was not only due to the reduced acidity but partially due to the more restricted pore openings, which might be caused by the aluminum species migration in alumina-bound ZSM-5 extrudates [20,31,36]. In the HZ-atp case, the extent of pore openings reduction decreased after regeneration, which indicated that the in-situ modification of acidity was the main reason for the increase of para-selectivity over HZ-atp.…”
Section: Resultsmentioning
confidence: 99%
“…Calculated from the saturation adsorption amounts, the n-hexane to cyclohexane adsorption ratio of HZ-bo increased from 1.8 to 1.9 after regeneration, whereas that of HZ-atp decreased from 1.9 to 1.7 after regeneration. It means that the initial para-selectivity increment for regenerated Z5-bo was not only due to the reduced acidity but partially due to the more restricted pore openings, which might be caused by the aluminum species migration in alumina-bound ZSM-5 extrudates [20,31,36]. In the HZ-atp case, the extent of pore openings reduction decreased after regeneration, which indicated that the in-situ modification of acidity was the main reason for the increase of para-selectivity over HZ-atp.…”
Section: Resultsmentioning
confidence: 99%
“…Acetic acid was added as a peptizing agent for the boehmite particles, to aid in mixing and adhesion with the zeolite particles. 52 The mixture was dried overnight at 120 °C in static air followed by calcination at 550 °C for 2 h with a ramp of 5 °C min –1 . Afterward, the product was crushed and sieved to obtain grains of 212–500 μm diameter.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For zeolitic materials, which have poor self‐binding properties, the inclusion of binders ‐ typically, alumina, silica or clays [16–17] ‐ is needed to attain durable catalyst bodies with the required strength and attrition resistance [18] . Yet, the selection of the specific binder or other additives, as well as the proportions used are of crucial importance, as they induce important modifications in the overall properties of the catalyst material and thus in activity [15,19–20] . Some examples of technical zeolite ZSM‐5 based catalysts extruded with clay minerals as binders can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%